Implementasi Kebijakan Program Desa Digital dalam Meningkatkan Pelayanan Publik di Desa Sidomulyo Kecamatan Silo Kabupaten Jember - Supriyono; Siswanto, Edhi (Indonesian Journal of Public Administration Review, 2023)
The concept of "digital village" refers to the use of ICT to drive digital transformation at the village or township level. The goal is to use technology to provide access, improve quality of life, and strengthen community empowerment in rural areas. The aim of this research is to explain and analyze how the implementation of the Digital Village Program policy improves public services in Sidomulyo Village, Silo District, Jember Regency. This research was conducted using a qualitative methodology combined with a descriptive approach. Observations, interviews and documentation were used to collect data. The village head, village officials and the community were the five research informants. George Edward III's theory of policy implementation is the one I use. First, the research results show that clear communication minimizes errors because there is no bias in conveying information. The aims and objectives of implementing the digital village program in Sidomulyo Village are very clear so that consistency can be created in building and developing the program from 2021 to 2023. Second, the resources needed to run the digital village program are already available because there are staff and all implementers who competent who can solve problems optimally. Third, the framework for implementing the digital village program in Sidomulyo Village is still limited to the village government and the Media Center team, so there is a lack of understanding of its implementation. Fourth, the bureaucratic structure involved in implementing the digital village program in Sidomulyo Village. This is caused by the lack of implementation and implementation of standard operating procedures (SOP) in each program that will be implemented. As a result, this process has not achieved maximum results.